2018
DOI: 10.1063/1674-0068/31/cjcp1805107
|View full text |Cite
|
Sign up to set email alerts
|

H2 dissociation by Au1-doped closed-shell titanium oxide cluster anions

Abstract: Dissociation of molecular hydrogen (H 2) is extensively studied to understand the mechanism of hydrogenation reactions. In this study, H 2 dissociation by Au 1-doped closed-shell titanium oxide cluster anions AuTi 3 O 7 − and AuTi 3 O 8 − has been identified by mass spectrometry and quantum chemistry calculations. The clusters were generated by laser ablation and massselected to react with H 2 in an ion trap reactor. In the reaction of AuTi 3 O 8 − with H 2 , the ion pair Au + −O 2 2− rather than Au + −O 2− is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For H 2 oxidation, it has been identified that the positively charged noble metal atom accounts for H 2 capture and then delivers H 2 for oxidation by the oxygen atom. 52 In this case, though the LUMO energies of Rh n VO 4 − are lower than those of Rh n O − (Fig. 7B), the positively charged and embedded Rh in atoms can be less facile for H 2 approach and then lead to the slower rates for reactions Rh 4–7 VO 4 − + H 2 with respect to Rh 4–7 O − + H 2 , especially for larger clusters (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…For H 2 oxidation, it has been identified that the positively charged noble metal atom accounts for H 2 capture and then delivers H 2 for oxidation by the oxygen atom. 52 In this case, though the LUMO energies of Rh n VO 4 − are lower than those of Rh n O − (Fig. 7B), the positively charged and embedded Rh in atoms can be less facile for H 2 approach and then lead to the slower rates for reactions Rh 4–7 VO 4 − + H 2 with respect to Rh 4–7 O − + H 2 , especially for larger clusters (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…, CH 4 , CO 2 , N 2 , H 2 , and C 3 H 8 ) induced by polarized metal–metal bonds is vital to have a comprehensive understanding on this unique bonding. 30,134–149 The studies on CH 4 activation and transformation mediated by a series of Rh-based HMOCs have been summarized in a recent review 17 and the importance of polarized Rh δ − –M (M = V and Ti) bonds was highlighted. For instance, the conversion of Rh δ + –O bonds in the RhAl 3 O 4 + cluster into Rh δ − –Al bonds in products RhAl 3 O 4 H 2 + (to release H 2 ) and RhAl 3 O 3 H 4 + (to release CO) is the driving force to rupture four C–H bonds of CH 4 and transform CH 4 into syngas (H 2 + CO), 134 and the formation of polarized Rh δ − –Ti bonds is crucial to functionalize CH 4 and CO 2 into syngas catalyzed by RhTiO 2 − .…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies also predicted that each of the clusters ZrScO 4 and ZrNbO 5 can oxidize only one CO molecule . A series of studies have identified that the E-ladder effect was also operative for the consecutive oxidation of two or more H 2 molecules by AuNbO 4 + , Au 2 VO 4 + , AuVO 4 + , and AuTi 3 O 8 – …”
Section: Resultsmentioning
confidence: 99%
“…87 A series of studies have identified that the E-ladder effect was also operative for the consecutive oxidation of two or more H 2 molecules by AuNbO 4 + , 88 Au 2 VO 4 + , 89 AuVO 4 + , 90 and AuTi 3 O 8 − . 91 Electronegativity is a fundamental concept in chemistry to predict the reactivity and charge transfer event among atoms and then guide the development of new materials. The research related to electronegativity has attracted great interest.…”
Section: +85mentioning
confidence: 99%